Cardiac Auscultation for Noncardiologists: Application in Cardiac Rehabilitation Programs. Issue 5 (September 2017) - Compostella, Leonida; Compostella, Caterina; Russo, Nicola; Setzu, Tiziana; Iliceto, Sabino; Bellotto, Fabio
Abstract : During outpatient cardiac rehabilitation after an acute coronary syndrome or after an episode of congestive heart failure, a careful, periodic evaluation of patients' clinical and hemodynamic status is essential. Simple and traditional cardiac auscultation could play a role in providing useful prognostic information. Reduced intensity of the first heart sound (S1), especially when associated with prolonged apical impulse and the appearance of added sounds, may help identify left ventricular (LV) dysfunction or conduction disturbances, sometimes associated with transient myocardial ischemia. If both S1 and second heart sound (S2) are reduced in intensity, a pericardial effusion may be suspected, whereas an increased intensity of S2 may indicate increased pulmonary artery pressure. The persistence of a protodiastolic sound (S3) after an acute coronary syndrome is an indicator of severe LV dysfunction and a poor prognosis. In patients with congestive heart failure, the association of an S3 and elevated heart rate may indicate impending decompensation. A presystolic sound (S4) is often associated with S3 in patients with LV failure, although it could also be present in hypertensive patients and in patients with an LV aneurysm. Careful evaluation of apical systolic murmurs could help identifying possible LV dysfunction or mitral valve pathology, and differentiate them from a ruptured papillary muscle or ventricular septal rupture. Friction rubs after an acute myocardial infarction, due to reactive pericarditis or Dressler syndrome, are often associated with a complicated clinical course. During cardiac rehabilitation, periodic cardiac auscultation may provide useful information about the clinical-hemodynamic status of patients and allow timely detection of signs, heralding possible complications in an efficient and low-cost manner. Abstract : The most significant common auscultatory findings in patients after acute coronary syndromes or with chronic heart failure are reviewed in relation to prognostic indicators. Cardiac auscultation may be an effective and inexpensive tool for periodic evaluation of patients during early outpatient cardiac rehabilitation.